PENERAPAN DIGITAL MARKETING BERBASIS FACEBOOK PADA UMKM KERUPUK SAGU - Asriani Asriani; Dhian Herdhiansyah; Syahria Rizka; Yandi Rismawan (Jurnal Abdi Insani, 2022)
MSMEs need attention in order to develop competitively. The development of information technology has changed the scope of the marketing world in recent years where marketing communication methods that were previously traditional and conventional have now been integrated into the digital world. Marketing activities that utilize the sophistication of digital technology are known as digital marketing. Digital marketing consists of interactive and integrated marketing that facilitates interaction between producers, market intermediaries and potential consumers, especially for MSMEs. This community service activity aims to apply online marketing strategies through a digital marketing system based on social media through the creation of a Facebook marketplace account for the sago cracker business in an effort to introduce new products to consumers and increase the market share of sago crackers. The implementation of the service is carried out through the identification stage of sago cracker MSME partners, formulating problem solutions, training on online marketing systems using the Facebook marketplace and conducting a survey of partner understanding and satisfaction. The results of the identification of partner problems are known that Annisa sago cracker MSMEs have not implemented an online marketing system. One of the solutions offered is to provide assistance in making the Facebook marketplace feature to assist in promotion. Based on the results of sago cracker MSME activities, they currently have a Facebook marketplace with the name "Sago Crackers Annisa" which can be used as a promotional medium in an effort to increase the market share of sago crackers.